Knowledge of Human Papillomavirus (HPV) and cervical cancer among Malaysia residents: a review - Nadzirah Nahrawi,; Siti Nurul Aqmariah Mohd Kanafiah,; Wan Azani Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cervical cancer is ranks as the third leading cause of female cancer deaths among women in Malaysia. Most of the cervical cases are caused by Human Papillomavirus (HPV) infection. To prevent HPV infection, Malaysia Government had implement Human Papillomavirus (HPV) vaccination program to all secondary school girls from 13 years old and above. The focus in this paper was to review the article based on the knowledge on HPV and cervical cancer among Malaysia resident before and after the implementation of HPV vaccine program. The knowledge about HPV, HPV vaccine, and cervical cancer after the implementation of national HPV vaccination program is better compare to before the program to be implemented. However, the knowledge is still poor among the respondents although there is an improvement after the program been implemented. The respondent gives a positive attitude towards HPV vaccination and cervical cancer screening. The main barrier of vaccination and Pap smear test are side effects, risk, cost, and effectiveness. In conclusion, knowledge about HPV and cervical cancer is really important among women. Education programs to the public are needed to enhance knowledge and to control the illness.